Comparative analysis of thermal distillation methods with heat pumps for long space flights - Rifert, V.G.; Anatychuk, L.I.; Barabash, P.O.; Solomakha, A.S.; Usenko, V.I.; Prybyla, A.V.; Petrenko, V.G.; Sereda, V.V. (Journal of Thermoelectricity, 2019)
The work compares technologies currently in use for water recovery from the vital products of astronauts in the conditions of long space missions. The advantage of using centrifugal thermal distillation is demonstrated. Possible failures and disadvantages of a compression vacuum centrifugal distiller compared with a centrifugal multistage distiller with a thermoelectric heat pump are shown. Bibl. 38, Fig. 3, Tabl. 2.